Hydrodynamic analysis on semi-submersible playform - Mohamad Farhan b Said, Mohamad Farhan (2010)
As the population increases exponentially and demand for inexpensive energy sources continue to raise, exploration and production for fossil fuel is rapidly growing. In order to meet the demands, the exploration has taken one step further to the extreme deep sea. Floating production platform design is a far more efficient and economical rather that fixed production platform at this depth.